APLIKASI PENGINDERAAN JAUH UNTUK ANALISIS PERUBAHAN PENGGUNAAN LAHAN KOTA PADANG TAHUN 2010 - 2020 - Putri, Dinda Emilsa; Juita, Erna; Zuriyani, Elvi (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2024)
This study aims to: 1) Assess the pattern of land use change in Padang City in 2010-2020. 2) Assess the factors that influence the pattern of change. 3) Assess the dynamics of land use during the same period. The method used is a quantitative descriptive approach with total sampling in all sub-districts in Padang City. Data analysis was conducted using spatial technique analysis (GIS) with overlay in ArcGIS and multiple linear regression analysis in SPSS. The results showed that: 1) In 2015, Padang City formed a uniform pattern, while in 2020 the pattern formed was random. 2) Factors that influence land use include population growth (1.6% in 2010-2015 and 0.84% in 2015-2020), population density (1,206 people/km² in 2010, 1,299 people/km² in 2015, and 1,308 people/km² in 2020), and the availability of socio-economic facilities. 3) Land use change from 2010 to 2020 shows a decrease in land area from 68,608.18 ha (2010) to 60,855.51 ha (2020), with an increase in organization and a decrease in dryland agriculture and primary dryland forest.